Antifeedant activity of Melia azedarach (L.) extracts to Diabrotica speciosa (Genn.)(Coleoptera: Chrysomelidae) beetles - Ventura,Maurício Ursi (2000)
Studies were carried out to determine the antifeedant activity of extracts of leaves, stems, flowers and fruits of Melia azedarach (L.), the dosage activity responses to the most active extract and the effects of sunlight in the activity persistence to Diabrotica speciosa (Genn.) beetles. Extracts efficiency was determined by evaluating leaf consumption. Insect feeding was deterred by stems, fruits and flowers extracts. Flowers and fruits extracts were the most efficient. Stems extract was in an intermediate position between the two most efficient and the least one (leaf extracts). The most active extract (flowers) was sprayed at concentrations of 0, 1, 2, 3, 4, 5, 6 and 7 g/100 ml. Feeding of D. speciosa on common bean leaves extracts decreased significantly with increasing concentrations of flowers extract, responding in a concentration-dependent manner. Two days after spraying, from 4 to 7 g/100 ml concentrations, feeding was totally inhibited. Four days after spraying, feeding occurred in 4-g/100 ml concentration. When common bean plants exposed to sunlight were sprayed with flowers extract (5-g/100 ml), beetles feeding increased gradually after extract spraying. Results showed that the lack of activity under sunlight conditions was a great limitation to use M. azedarach aqueous extracts.